Performance management at Perelson Weiner LLP - Bell, Jan, (SAGE Knowledge. Cases., 2017)
This case describes various aspects of the strategic performance management system in place at a small, "boutique" CPA firm. Ron Weiner, the managing partner at Perelsen Weiner, is very clear about his company's strategic position, with a precise notion about the niche the company serves, including the services it offers, the target market, and the value proposition. Unlike the typical case where a decision maker faces a dilemma or task, here Ron Weiner is quite adamant about the optimal performance management system design for his firm. His focus is on simplicity, and he rejects the need for complicated, but trendy, tools like ABC or the Balanced Scorecard. The student's task is to follow the logic presented in the case, evaluate it, and debate the design in the classroom.